INDUSTRIAL ARCHITECTURE OF ODESSA FROM THE CONTEXT OF RENOVATION OF INDUSTRIAL OBJECTS (Advances in Civil and Architectural Engineering, 2021)
This paper discusses the importance of studying and rethinking the history of the development of domestic industrial architecture. The chronology of the development of industrial architecture in Odessa against the background of the industrial history of Russia and Ukraine is considered. The main stages and time frames typical for Odessa are identified as pre-industrial (1791–1861), the stage of formation (1861–1917/20), industrial (1918/20–1985), and post-industrial (1986–present day). The paper presents a brief description of each stage along with the analysis of the current state of industrial architecture. In addition, the experience of the renovation of industrial facilities in Odessa is considered, and the main spectrum of new functions is revealed. Two types of renovation objects are identified: historically significant and typical. The renovation is considered as a method of stabilizing urban space.